Truth seeking and reconciliation importance of truth for post-war peace building in sri lanka - Asiri, D.V.M.S. (University of Jaffna, 2012)
This study examines the importance of seeking truth, for the post war reconciliation process in Sri Lanka. Both questionnaires and interviews were used to collect quantitative and qualitative data, as the study used mixed methods. During the first step of analysis, data was edited and coded. Then, quantitative data were analysed by using spread sheets as percentage analysis. Qualitative data was analysed by using context analysis. The study used probability sampling and non-probability sampling methods to have a sample of the large population, as it is hard to have a sample frame for a dispersed population. As a result, samplings were focused on characteristics of the population such as ethnicity, gender and place of resident to have smaller elements. The study focused on Tamil ethnicity in Northern Province, Muslim ethnicity in Eastern Province and Sinhala ethnicity in Southern province. However, according to the responses, 92.8% of all ethnic communities believed that reconciliation is possible with the present condition in Sri Lanka. The Sri Lankan ethnic conflict began between Sinhala and Tamil ethnic groups and ethnic based polarization continued throughout ethnic groups. In order to understand how to address the problem of polarization and how to reconcile the society, it is necessary to get to know about the past truth and understand each other. 79% of Sri Lankan ethnic communities are willing to express their past truth with the hope of justice and heal themselves. The study found that people are ready to speak about past and understand each other. However, they fear it will be a danger to their lives. Also, the study revealed that people are willing to understand each other and build a shared future together. So, on the basis of this study for reconciliation in Sri Lanka, an experimental model for truth is proposed. The study also recommends a victim protecting system with legal conventions so that people can speak about their past truth without any hesitation.
Keywords: Post war peace building; Reconciliation; Sri lanka; Truth seeking